2018
DOI: 10.5539/ijel.v8n3p177
|View full text |Cite
|
Sign up to set email alerts
|

English Language Teaching and Cultural Implications in Saudi Arabia

Abstract: Culture and language are inseparable. Language is used both as a means of communication as well as a carrier of culture. Language without culture is unthinkable, so is human culture without language (Wei, 2005). While teaching a foreign language, a teacher needs to accustom himself with the culture of the target language and the culture of learners. However, teachers in different classrooms in different parts of the world still ignore the importance of culture as a part of language study. This study focuses on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…In constant with Hui's (2010) findings, the results revealed teachers' willingness and readiness to engage in cultural teaching while some problems were observed in their perception of some aspects linked with the activities employed, the assessment methods used, and the cultural teaching practices. The findings also go hand in hand with Farooq, Soomro, and Umer's (2018) results, which revealed that teachers are aware of integrating culture and language in their teaching.…”
Section: Discussionmentioning
confidence: 57%
“…In constant with Hui's (2010) findings, the results revealed teachers' willingness and readiness to engage in cultural teaching while some problems were observed in their perception of some aspects linked with the activities employed, the assessment methods used, and the cultural teaching practices. The findings also go hand in hand with Farooq, Soomro, and Umer's (2018) results, which revealed that teachers are aware of integrating culture and language in their teaching.…”
Section: Discussionmentioning
confidence: 57%
“…Only one instrument is used in the study, which is a questionnaire instrument. This questionnaire instrument was adapted and modified based on the instrument built by Farooq et al (2018). It consisted of three sections: (A) the background information of the respondent: GIL secondary school teachers' personal information, educational background and teaching experience of the respondent, (B) 15 items about the GIL secondary school teachers' perceptions regarding the importance of teaching German culture in GIL classroom, and (C) 14 items about GIL secondary school teachers' classroom activities.…”
Section: Methodsmentioning
confidence: 99%
“…Integrating culture into FL or L2 teaching is an area in language research that attracted the attention of many scholars and researchers during the last decades (Byram & Kramsch, 2008;Farooq et al, 2018;Liddicoat & Scarino, 2013;Nguyen et al, 2016;Putra & Musigrungsi, 2022). The application or involvement of cultural aspects in teaching foreign languages has long been debated by scholars.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Arab learners perceive writing in the traditional style, abiding by rules and a specific structure (Altheneyan & Boayrid, 2019). Farooq et al (2018) also found that culture plays a significant role when a learner learns English as a foreign language; it becomes essential to understand the target language's culture to express thoughts, ideas, and feelings copiously.…”
Section: Research Studies On Iep Academic Writing Skills-mentioning
confidence: 99%